Neologisms in Virtual Discourse, Their Structural and Semantic Characteristics - Дячук, Т.; Литвинська, С. (Київський національний університет імені Тараса Шевченка, 2024)
Ваckground. The relevance of the study of neological lexicon is determined by the need to constantly organize the formal level of the lexical-semantic system of the language. Methods. Factual material was selected using a continuous sampling method from various sources (see list of sources used). The descriptive method was used to study the features of communication in the virtual environment, the induction method was used to generalize and draw conclusions, and the method of structural analysis was used to identify ways of creating new vocabulary. Results. The article analyzes neologisms selected from online media from the point of view of structure, semantics, and origin. Neolexems were found to be multi-structured (words, juxtapositions, especially many abbreviations, word combinations). From the point of view of origin, borrowings from the English source language continue to dominate. Neolexes of Ukrainian origin are extremely few. The process of expanding the semantic structure of some commonly used words continues. Conclusions. Online media is an important source of formation and functioning of neolexes. The prospect of neologism research is obvious. The problem of adequate replacement of neologisms of foreign origin with Ukrainian equivalents, development of effective mechanisms of "promotion" of Ukrainian names from the sphere of fixation to the sphere of functioning is particularly relevant.

Вступ. Актуальність дослідження неологічної лексики зумовлена необхідністю постійного впорядкування формального рівня лексико-семантичної системи мови. Методи. Фактичний матеріал був відібраний за допомогою методу суцільної вибірки з різних джерел (див. список використаних джерел). Для вивчення особливостей комунікації у віртуальному середовищі використовувався описовий метод, для узагальнення та підбиття підсумків – метод індукції, для виявлення способів творення неологічної лексики – метод структурного аналізу. Результати. У статті проаналізовано неологізми, відібрані з онлайн-ЗМІ, з погляду структури, семантики, походження. Виявлено, що неолексеми різноструктурні (слова, юкстапозити, особливо багато абревіатур, словосполучення). З погляду походження продовжують домінувати запозичення з англійської мови-джерела. Неолексем українського походження надзвичайно мало. Продовжується процес розширення семантичної структури окремих загальновживаних слів. Висновки. Онлайн-ЗМІ – важливе джерело утворення та функціонування неолексем. Перспектива досліджень неологізмів очевидна. Особливо актуальною є проблема адекватної заміни неологізмів іншомовного походження на українські відповідники, напрацювання дієвих механізмів «просування» українських назв зі сфери фіксації у сферу функціонування.
Неологізми у віртуальному дискурсі, їхня структурно-семантична характеристика
Keywords: neologism; sphere of fixation; sphere of functioning; foreign word; borrow-ing; semantic structure of the word; неологізм; сфера фіксації; сфера функціонування; іншомовне слово; за-позичення; семантична структура слова